Volumetric Evaluation of Maxillary Lateral Incisor Root Resorption due to Positional Variations of Impacted Canine - Mohammed Hossein Razeghinejad; Roghieh Bardal; Saeid Shahi; Elham Mortezapoor; Maryam Mostafavi (Hindawi Limited, 2022)
Introduction. The purpose of this study was to investigate the relationship of the volume of lateral incisor resorption and impacted canine features. Materials and Methods. This study consisted of CBCT images of 47 samples with unilateral impacted maxillary canine (13 males and 34 females). The volume of lateral incisors in impacted side and nonimpacted side was calculated with the Mimics 10.01 software. Canine and lateral incisor angulations were measured in panoramic reformatted images. The canine cusp tip distance from midpalatal suture was measured in axial cross-section images. Results. The difference between two sides volume was considered as the mean volume of resorption (MVR) that was statistically significant (P<0.001). MVR was not statistically significant between two sexes (P=0.95), in buccopalatal and mesiodistal positions of impacted canine, and in different angulations or distances of the impacted canine to midline (P>0.05). The concurrent effect of the canine distance to the midline and the angle of the canine with the lateral incisor on the MVR were statistically significant (P=0.049). Conclusion. The maximum rate of lateral root resorption is when the distance from the canine to the midline is less than 5 mm and the angle of the canine to the lateral incisor is 30-60 degrees.